Determinants of student achievements in the primary education of Paraguay - Thomas Otter; Carlos Villalobos Barría (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2009)
The idea that schooling scores depend on a combination of family background characteristics, ability and school (institutional) variables is quite clear. Regarding the issue of intergenerational transmission of inequality in the educational system, the most important question would be if and to what extent could a better institutional performance of the school service compensate for problems related to family background. By means of the estimation of a reduced form equation for selected scores, we investigate the impact of institutional performance on scores after controlling for family background and individual characteristics. We do this by using a novel data set and an OLS and quantile regression approach to analyze how heterogeneous the process of score generation can be. By providing integral health solutions, minimizing under-nutrition and providing ideal conditions in the classroom, training teachers can impact positively on low and mean learning outcomes, thus contributing to an improved educational quality and breaking cycles of intergenerational transmission of inequality. Increasing learning outcomes for levels above the median, only strengthens the transmission of inequality. Consequently, the equality approach should focus on trying to improve the worst scores and our results show that this can be reached at a significant level closing teacher training gaps, improving classroom conditions and improving health and nutrition.
Keywords: A21; H52; I21; I28; 330; Reduced-Form Production Function; Educational outcomes; Inequality; Bildungsniveau; Allgemeinbildende Schule; Bildungsökonomik; Produktionsfunktion; Schätzung; Paraguay